HIV Disrupts Human T Cells That Target Mycobacterial Glycolipids. (15th September 2015) - Kasprowicz, Victoria O.; Cheng, Tan-Yun; Ndung'u, Thumbi; Sunpath, Henry; Moody, D. Branch; Kasmar, Anne G.
Abstract : Single-cell analysis captures the heterogeneity of T-cell populations that target defined antigens. Human immunodeficiency virus (HIV) infection results in defects of antimycobacterial immunity, which remain poorly defined. We therefore recruited a small number of subjects, including those with latent and active M. tuberculosis infection, with or without concomitant HIV infection, and tracked the mycobacterial glycolipid-reactive T-cell repertoire by using CD1b tetramers. Glycolipid-reactive T cells expressed memory markers and the HIV coreceptors CD4 and CCR5; they were not detected in subjects with HIV-associated active M. tuberculosis infection. HIV infection may affect T cells that recognize mycobacterial glycolipids and influence immunity.